Paramyxovirus Fusion and Entry: Multiple Paths to a Common End - Rebecca E. Dutch; Andres Chang (Viruses, 2012)
The paramyxovirus family contains many common human pathogenic viruses, including measles, mumps, the parainfluenza viruses, respiratory syncytial virus, human metapneumovirus, and the zoonotic henipaviruses, Hendra and Nipah. While the expression of a type 1 fusion protein and a type 2 attachment protein is common to all paramyxoviruses, there is considerable variation in viral attachment, the activation and triggering of the fusion protein, and the process of viral entry. In this review, we discuss recent advances in the understanding of paramyxovirus F protein-mediated membrane fusion, an essential process in viral infectivity. We also review the role of the other surface glycoproteins in receptor binding and viral entry, and the implications for viral infection. Throughout, we concentrate on the commonalities and differences in fusion triggering and viral entry among the members of the family. Finally, we highlight key unanswered questions and how further studies can identify novel targets for the development of therapeutic treatments against these human pathogens.